Influence of Governing Body Structure on Financial Sustainability of NGOs in the Advocacy Sector in Kenya - Aidah, Alice Wangui; Waiganjo, Esther; Njeru, Agnes (European Scientific Journal, ESJ, 2026)
Purpose: The study sought to examine the influence of governing body structure on the financial sustainability of NGOs in the advocacy sector in Kenya. Methodology: The study utilised a mixed-methods research approach and adopted a cross-sectional survey design. The study’s target population was 11,176 NGOs in the advocacy sector in Kenya, using a sample size of 384 NGOs, based on the Taro Yamane formula. 305 responses were received and analysed. Research instruments included questionnaires and checklists used to triangulate responses from questionnaires. Qualitative data was analyzed and presented in narrative statements, while inferential statistics were analyzed using the Pearson correlation coefficient and multiple regression analysis to test hypotheses. Findings: From the descriptive statistics, professional diversification of board members was highly agreed upon by respondents as having an influence on financial sustainability of NGOs in the advocacy sector in Kenya while board members diversification by age was the least agreed upon item. The study found a positive significant correlation between governing body structure and financial sustainability. The regression results also found that governing body structure explained a substantial amount of variance in financial sustainability of NGOs in the advocacy sector in Kenya. The study rejected the null hypothesis and concluded that governing body structure has significant influence on the financial sustainability of NGOs in the advocacy sector in Kenya. Recommendations: Managers in NGOs in the advocacy sector should develop systems that promote the structure of the governing body structure by ensuring that the number of members of the governing body are neither too few nor too many to impede deliberations during meetings. Members should hold regular meetings and the membership of the governing should also be diversified in terms of expertise and should be independent from management. In addition, CEOs should not play the dual role of also being the Chair of the governing body.